Educational and professional motivation as a part of professional formation of future specialists of pedagogical specialization (Pedagogy of Higher and Secondary Education, 2016)
Onishchenko I. V. Educational and professional motivation as a part of professional formation of future specialists of pedagogical specialization.The interest in teaching profession and its development is one of the important factors of successful learning and future professional self-development. Educational and professional motivation is important in teacher’s professiogram. The aim of the article is to analyse the socio-psychological characteristics of educational and professional motivation for future pedagogical specialists, define the role of educational and professional motivation in the system of future teachers training. Research methods are the analysis of state standards, statistics and scientific publications. Analyzed social-psychological characteristics of educational and professional motivation of future teachers showed the conditions of its formation in terms of high school. Educational and professional motivation requires integration, interests, incentives, values and motivations which encourage and guide person in msatering future profession. The direction of development and transformation of the motivational structure of students’ personality formation during the educational process is determined by the number of specific factors, such as educational system, educational institutions, organization of educational process, personal characteristics of students, personal characteristics of teachers, specific academic subjects. It was proved that educational and professional motivation is the internal driving factor of professionalism formation and a leading factor in successful learning at secondary school.Formation of educational and professional motivation of future specialists of pedagogical specialization is an essential component of training. It provides students with fundamental knowledge, professional skills, active, conscious affirmation of professional choice. Educational and professional motivation is a dynamic system that changes according to the stages of professional development of the individual. Training of teachers must make the transition from teaching and learning to the professional development with corresponding changes in motivations, goals, means, subjects and results. Prospects for further research are aimed at studying the place of motivational component in the structure of readiness of the future teacher to innovative professional activities.
Keywords: motive; motivation; educational and professional motivation; learning activities; professional activities; professional training; professional development and teacher